The Genealogy of the Taradhin Concept within the Five Pillars of Tepuk Sakinah: An Islamic Family Psychology Perspective - Mohammad Saiful Rifai; Lusi Andriani; Vivit Vidayanti; Benny Prasetiya (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2025)
This study aims to trace the genealogy of the taradhin concept within the discourse of the Five Pillars of Tepuk Sakinah promoted by the Indonesian Ministry of Religious Affairs (Kemenag) and to analyze its implications for Islamic family psychology. Taradhin (mutual consent) represents the fifth pillar in Kemenag’s Bimbingan Perkawinan (Pre-Marital Guidance) program, symbolizing balance and acceptance in marital relations. However, the transformation of this concept from classical spirituality to an institutional norm raises critical questions about its function, meaning, and psychological impact on couples’ well-being. This research employs a qualitative approach based on library research and uses Michel Foucault’s genealogical analysis. Data sources include official Kemenag documents, the Bimwin module, Tepuk Sakinah lyrics, and classical as well as modern literature on Fiqh and Positive Psychology. The analysis proceeded in three stages: archaeological mapping, genealogical deconstruction, and substantive interpretation. The findings reveal a shift in the meaning of ridha from a vertical spiritual dimension toward taradhin as a horizontal, institutionalized norm. Kemenag, as an apparatus of power-knowledge, normalizes taradhin through Tepuk Sakinah as a disciplinary technique designed to produce obedient sakinah family subjects. Functionally, mutual taradhin supports marital satisfaction and psychological well-being, yet when imposed repressively, it risks generating “false sakinah” that suppresses autonomy and emotional expression. Taradhin holds positive psychological potential for Islamic families if internalized consciously and equitably rather than as a disciplinary norm. Reformulating the taradhin discourse is essential to emphasize self-ethics, equality, and genuine psychological well-being within marital life.